Pemeriksaan Tekanan Darah Dan Edukasi Tentang Penyakit Hipertensi Pada Masyarakat Desa Moleono, Kabupaten Morowali Utara, Provinsi Sulawesi Tengah - Yulian Heiwer Matongka; Ida Yanriatuti; Sabarulin (AMMA : Jurnal Pengabdian Masyarakat, 2026)
Hypertension, or high blood pressure, remains a global health problem. In Central Sulawesi province, hypertension is the most prevalent non-communicable disease. Similarly, North Morowali Regency has the highest number of non-communicable disease cases, with only 6.4% of the population regularly seeking health care. Left untreated and untreated, hypertension can lead to various dangerous complications, even death. Given this problem, efforts are needed to help lower blood pressure in hypertension sufferers. One way is to provide information and knowledge about the dangers of hypertension. This will increase public awareness and enhance the ability to address their hypertension. Therefore, through this community service, efforts were made to provide health education on hypertension and conduct direct blood pressure checks in the community in Moleono Village, West Petasia District, North Morowali Regency, Central Sulawesi Province. The results of this community service showed that many people suffer from hypertension, namely 44.28% of all participants. The community also actively asked questions during the health education and expressed a desire to obtain antihypertensive medication. Health education and blood pressure measurements are crucial for preventing an increase in prevalence, maintaining blood pressure control, and preventing complications.